Gay Black Men at Midlife: Learning Self Acceptance - Lorenzo Bowman; Lawrence Bryant (Adult Education Research Conference, 2010)
This paper presents the findings of an analysis of three autoethnographies of Black gay men at midlife. The findings indicate that Black gay men experience themselves as silenced from an early age. Further, Black gay men actively work to conceal their sexual orientation in response to social expectations. Black gay men “evolve” to a point of self acceptance at midlife rather than abruptly “coming out” and Black gay men reach out to their communities at midlife in an apparent need to give back.